Low-dose esketamine for the prevention of emergency agitation in children after tonsillectomy: A randomized controlled study - Qi Li; Jiaming Fan; Wangping Zhang (Frontiers Media S.A., 2022)
Background: Emergency agitation is a common postoperative complication in pediatric patients after general anesthesia. The aim of this study was to explore the effects of a low dose of esketamine on emergency agitation in children following tonsillectomy.Materials and Methods: Eighty children were recruited prospectively to this study and divided into the esketamine group and the control group (40 cases in each group). The induction and maintenance of anesthesia were the same in both groups. At the end of surgery, the esketamine group received 0.25 μg/kg esketamine, while the control group received the same volume of normal saline. The extubation time, time to eye opening, Ramsay sedation scale and time to discharge from the post-anesthesia care unit (PACU) were recorded during post-anesthesia care unit. Postoperative complications, such as emergency agitation, respiratory depression, hypertension, tachycardia, nightmares, nausea, and vomiting, were also recorded.Results: The incidence of emergency agitation was lower in the esketamine group compared with that in the control group (5% vs. 27.5%, p = 0.006). The time to eye opening was longer in the esketamine group than in the control group (17.2 ± 2.7 vs. 15.5 ± 2.3 min, p = 0.005). However, the extubation time and time to discharge from PACU were similar between the two groups.Conclusion: Low-dose of esketamine decreases the incidence of emergency agitation in children after tonsillectomy without delaying extubation time and increasing the postoperative side effects. (www.chictr.org.cn, registration number: ChiCTR2100054178).